Non-Destructive Testing of the Quality of Wooden Columns in Zeng Jingyi’s Ancient Wooden Structures - Jing Yang; Shaojie Wu; Yingcai Fang; Benhuan Xu; Zheng Wang (BioResources)
This study focuses on the wooden columns of a historic residential structure to assess their integrity. Employing non-invasive computed tomography (CT) scanning, the internal integrity of these ancient wooden supports was examined. Stress wave analysis, pilot nail testing, and assessments of static bending and compressive mechanical performance were performed to validate and compare the data. The findings revealed substantial variability in the material quality across the columns’ cross-sections, suggesting a loss of mechanical integrity that renders them unsafe for habitation or public access. A comparison between the CT scan outcomes for the Masson’s pine columns and the stress wave data from the dismantled counterparts confirmed a marked degradation in their mechanical characteristics, rendering them unfit for use. The CT scan findings align with the pilot nail test results, both accurately pinpointing the condition and precise locations of defects within the columns. The static mechanical performance tests substantiated the precision and dependability of the CT scanning, pilot nail testing, and stress wave analysis in evaluating the wooden columns’ quality. This research aims to establish a scientific foundation for employing diverse non-destructive testing methods in the preservation and strengthening of traditional wooden structures, thereby safeguarding our cultural heritage.